1996
DOI: 10.1029/96jb00817
|View full text |Cite
|
Sign up to set email alerts
|

Major crustal rotations in the Andean margin: Paleomagnetic results from the Coastal Cordillera of northern Chile

Abstract: Paleomagnetic analyses of Mesozoic lavas and dike swarms from the northern Chilean Coastal Cordillera, between 25.4°S and 26.4°S, reveal a clockwise rotation of about 42°. Magnetizations from lava flows of andesitic‐basaltic composition of the Middle Jurassic La Negra Formation pass both fold and reversal tests and are interpreted as prefolding remanences. Five dike swarms of Middle Jurassic to Early Cretaceous age yield similar directions to that obtained from the La Negra Formation. Four of the five swarms h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 56 publications
(17 reference statements)
1
54
0
Order By: Relevance
“…In the other hand, the Paleogene deformation is more widely distributed across the Andes of northern Chile (Arriagada et al, 2000(Arriagada et al, , 2003(Arriagada et al, , 2006bTaylor et al, 2007). Eocene-Oligocene deformation was accompanied by tectonic shortening, mountain uplift and significant clockwise block rota tions (e.g., Hartley et al, 1992;Riley et al, 1993;Forsythe and Chisholm, 1994;Randall et al, 1996;Taylor et al, 1998;Arriagada et al, 2000;Somoza and Tomlinson, 2002;Arriagada et al, 2003Arriagada et al, , 2006bArriagada et al, , 2008. Fission track thermochronology indicates that tectonic uplift and erosion were mainly active during the EoceneEarly Oligocene 'Incaic Orogeny', when at least 4-5 km of rocks were eroded during exhumation of tectonic blocks of the Cordillera de Domeyko between ca.…”
Section: Introductionmentioning
confidence: 99%
“…In the other hand, the Paleogene deformation is more widely distributed across the Andes of northern Chile (Arriagada et al, 2000(Arriagada et al, , 2003(Arriagada et al, , 2006bTaylor et al, 2007). Eocene-Oligocene deformation was accompanied by tectonic shortening, mountain uplift and significant clockwise block rota tions (e.g., Hartley et al, 1992;Riley et al, 1993;Forsythe and Chisholm, 1994;Randall et al, 1996;Taylor et al, 1998;Arriagada et al, 2000;Somoza and Tomlinson, 2002;Arriagada et al, 2003Arriagada et al, , 2006bArriagada et al, , 2008. Fission track thermochronology indicates that tectonic uplift and erosion were mainly active during the EoceneEarly Oligocene 'Incaic Orogeny', when at least 4-5 km of rocks were eroded during exhumation of tectonic blocks of the Cordillera de Domeyko between ca.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors (Beck et al, 1994;Butler et al, 1995) developed models which combine oroclinal bending and local block rotations, then each locality would record a local amount of rotation plus a regional (orocline related) rotation. Domino-style models that relate the rotations detected in northern Chile to observable faults in the forearc have also been published (e.g., Forsythe and Chisholm, 1994;Randall et al, 1996;Taylor et al, 1998;Abels and Bischoff, 1999). However, Arriagada et al (2003) found clockwise tectonic rotations of up to 65° within the forearc domain (Antofagasta region), which would have occurred mainly during the Incaic orogenic event of Eocene-Early Oligocene age.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The rocks of the Coastal Cordillera record some of the largest paleomagnetic rotations in the Andes [Forsythe and Chisholm, 1994;Forsythe et al, 1987;Randall et al, 1996;Taylor et al, 1998]. The study area lies at the southern limit of the Central Valley between 26.5 and 27.5°S and east of the city of Copiapó (Figures 2 and 3).…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%
“…R is the calculated rotation compared to the appropriate reference 5 Ma synthetic poles from Besse and Courtillot [2002] and its associated error [Demarest, 1983]. Sources of data are 1, Arriagada et al [2006]; 2, Riley et al [1993]; 3, Randall et al [2001]; 4, Randall et al [1996]; 5, Forsythe et al [1987];6, Taylor et al [1996]. sinistral faults and lineaments which could have accommodated clockwise rotation during margin normal contraction [Abels and Bischoff, 1999;Forsythe and Chisholm, 1994;Grocott and Taylor, 2002;Randall et al, 1996;Taylor et al, 1998].…”
Section: Comparison Of the Copiapó And The Antofagasta Regionsmentioning
confidence: 99%
See 1 more Smart Citation